Harry's monkey - Willson, Robina Beckles; Catchpole, Diana (Heinemann Oxford, 1996)
Part of the "Storyworlds" series, this is a pack of the four Stage Six stories about animal charcters. Each story reinforces between 20 and 40 new words, and adopts a broadening approach, to encourage the move to independent reading. Continued repetition of text should to help build confidence.